2019
DOI: 10.1038/s41598-019-55982-2
|View full text |Cite
|
Sign up to set email alerts
|

Discordant gene responses to radiation in humans and mice and the role of hematopoietically humanized mice in the search for radiation biomarkers

Abstract: The mouse (Mus musculus) is an extensively used model of human disease and responses to stresses such as ionizing radiation. As part of our work developing gene expression biomarkers of radiation exposure, dose, and injury, we have found many genes are either up-regulated (e.g. CDKN1A, MDM2, BBC3, and CCNG1) or down-regulated (e.g. TCF4 and MYC) in both species after irradiation at ~4 and 8 Gy. However, we have also found genes that are consistently up-regulated in humans and down-regulated in mice (e.g. DDB2,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 73 publications
0
31
0
Order By: Relevance
“…In agreement with comparative data of the mouse and human p53 GRN [7], a recent gene expression profiling study showed that the regulation of p53 target genes differed substantially between mouse and human blood samples in response to gamma radiation. Yet, the response was similar between blood samples from humans and humanized mice engrafted with hematopoietic stem cells [15], further supporting the use of humanized mouse models to generate data that are more meaningful to humans.…”
Section: Bridging the Gap Between Mouse And Humanmentioning
confidence: 62%
“…In agreement with comparative data of the mouse and human p53 GRN [7], a recent gene expression profiling study showed that the regulation of p53 target genes differed substantially between mouse and human blood samples in response to gamma radiation. Yet, the response was similar between blood samples from humans and humanized mice engrafted with hematopoietic stem cells [15], further supporting the use of humanized mouse models to generate data that are more meaningful to humans.…”
Section: Bridging the Gap Between Mouse And Humanmentioning
confidence: 62%
“…These species-related considerations are especially important when considering that recent studies have shown that the gene responses to radiation (e.g. in the blood) vary greatly across different species 60 .…”
Section: Discussionmentioning
confidence: 99%
“…These species-related considerations are especially important when considering that recent studies have shown that the gene responses to radiation (e.g. in the blood) vary greatly across different species 53 .…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, these molecular and neuropathological ndings observed 4 weeks following low-dose total-body radiation in a large mammalian brain are unique and of special relevance for possible future therapeutic applications to Approximately two weeks after arrival, swine receiving total-body radiation were deeply anesthetized with Ketamine/Xylazine (4.4mg/kg-2mg/kg) and transported to the High Level Cobalt facility at (A liations removed for Peer Review). While under deep anesthesia, swine were positioned in supportive slings and exposed one at a time, bilaterally, to a target total body dose of 1.79 Gy of Cobalt ( 60 Co) radiation delivered at a dose rate of 0.485-0.502 Gy/min as previously described 53 . After radiation procedures, each animal was transported back to the animal facility for recovery.…”
Section: Discussionmentioning
confidence: 99%